Occupational attainment and immigrant economic progress in Australia - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2008)
Using data from the 2001 Australian Census of Population and Housing, on adult men in full-time employment, this paper augments a conventional human capital earnings function with information on occupations. It also estimates models of occupational attainment. The results from both the earnings function and model of occupational attainment indicate that the limited international transferability of human capital skills results in immigrants entering into relatively low status occupations when they first enter the Australian labour market. Comparison with similar research for the US suggests that the different immigrant selection regimes (primarily family reunion in the US, skill-based immigration in Australia) do not impact on the negative association between occupational status and pre-immigration labour market experience.
Keywords: J24; 330; Immigrants; occupation; earnings; Migranten; Männliche Arbeitskräfte; Qualifikation; Berufswahl; Einwanderung; Lohnstruktur; Australien